2008
DOI: 10.1038/emboj.2008.22
|View full text |Cite
|
Sign up to set email alerts
|

ShcA signalling is essential for tumour progression in mouse models of human breast cancer

Abstract: To explore the in vivo significance of ShcA during mammary tumorigenesis, we used mice expressing several phosphotyrosine-deficient ShcA alleles under the control of their endogenous promoter. We show that all three ShcA tyrosine phosphorylation sites are involved in the early stages of mammary tumour progression, including loss of the myoepithelial cell layer surrounding hyperplasias and during progression to carcinoma. We have determined that signals emanating from Y313 are important for tumour cell survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
213
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 134 publications
(225 citation statements)
references
References 42 publications
11
213
1
Order By: Relevance
“…We have previously shown that the MMTV/NIC strain develops metastatic mammary tumors with comparable latency to other MMTV/activated ErbB2 strains (Ursini- Siegel et al, 2008). Because NIC transgene also co-express Cre recombinase due to the presence of internal ribosome entry site (IRES), mammary epithelial cells expressing activated ErbB2 will excise the conditional ILK allele (Ursini- Siegel et al, 2008). Thus the coupled expression of ErbB2 and Cre recombinase precludes the possibility of obtaining ErbB2-expressing Crenegative 'escapee' populations that could possibly contribute to the tumor.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…We have previously shown that the MMTV/NIC strain develops metastatic mammary tumors with comparable latency to other MMTV/activated ErbB2 strains (Ursini- Siegel et al, 2008). Because NIC transgene also co-express Cre recombinase due to the presence of internal ribosome entry site (IRES), mammary epithelial cells expressing activated ErbB2 will excise the conditional ILK allele (Ursini- Siegel et al, 2008). Thus the coupled expression of ErbB2 and Cre recombinase precludes the possibility of obtaining ErbB2-expressing Crenegative 'escapee' populations that could possibly contribute to the tumor.…”
Section: Resultsmentioning
confidence: 95%
“…We have previously shown that ectopic expression of ILK results in induction of metastatic mammary tumors that possess the hallmarks of an EMT phenotype (White et al, 2001). Using an ErbB2 transgenic model (Ursini- Siegel et al, 2008), we have shown that mammary epithelial disruption of ILK resulted in a dramatic delay in mammary tumor induction. Analyses of premalignant ErbB2-expressing mammary epithelium lacking ILK function has revealed that this block in ErbB2 tumor induction is associated with profound block in epithelial proliferation (Figure 2d, Supplementary Figure S2).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations